Is permanent congenital facial palsy caused by birth trauma? - Laing, J H; Harrison, D H; Jones, B M; Laing, G J (Archives of disease in childhood, 1996)
OBJECTIVE: To study the relation between traumatic birth and the development of permanent facial palsy in the newborn. DESIGN: Retrospective case control study of children with 'congenital' facial palsy. SETTING: Two tertiary referral centres for patients with facial palsy. SUBJECTS: 61 children with established facial palsy. MAIN OUTCOME MEASURES: Odds ratios of recognised factors for birth injury: maternal primiparity, high birth weight, and the use of obstetric forceps at delivery. RESULTS: 13.2% of those studied had forceps assisted delivery compared to 10.2% in the normal population (odds ratio 1.34; 95% confidence intervals 0.61 to 2.97) 39.6% were born to primiparae compared to a national rate of 36.7% (1.13; 0.65 to 1.96) and only 18.9% weighed more than 3500 g at birth (0.37; 0.19 to 0.74). CONCLUSIONS: There is no association between the development of permanent 'congenital' facial palsy and recognised risk factors for birth injury. These data suggest an intrauterine rather than a traumatic aetiology.